P-023. Changing of HAV seroprevalence in special young age group (health vocational high school students) - Tosun, Selma (Turk J Gastroenterol, 2019)
INTRODUCTION: Hepatitis A virus (HAV) infection is the most common cause of viral hepatitis worldwide but major geographic differences exists in endemicity. Turkey is accepted in moderate endemicity group. Incidence of HAV infection is shown to decrease in Turkey and the disease age is shifting to an advanced age. In this study we aimed to evaluate HAV seropositivity and vaccination status of health vocational high school students. METHODS: Students ages between 17–24 who were in of health vocational high school students at hospital clinics were included in the study. After informed consents and ethical commity aprovals were taken, all students filled a questionnaire about sociodemographic features, knowledge and vaccination history of HAV infection. Serum anti-HAV IgG were measured by an enzyme linked immunoassay. FINDINGS: A total of 513 students were included in the study. Serological results revealed that 23% of students were immunized for HAV thus 77% was still susceptible to infection. Only eight of the seropositive students were vaccinated, and the rest naturally had the disease. All data are shown in the table. CONCLUSION: The incidence of HAV infection is decreasing in Turkey and the disease age is shifting to an advanced age thus leading to the development of a large susceptible population to infection in older population. CDC recommends overall HAV vaccination to low and intermediate endemicity areas and Turkey started routine infant vaccination by the year of 2013. In our study, 77% of student population were found susceptible to HAV infection and all of the seronegative students were vaccinated to HAV. This study show that HAV infection epidemiology is changing in adolescents and young adults in our region. In addition, HAV vaccination are becoming more important for these young people as they are candidates for health care workers.